INGLIS HÁM QARAQALPAQ TILLERINDE “SÓYLEW/SPEECH” KONCEPTOSFERASÍNÍŃ SALÍSTÍRMALÍ ÚYRENILIWI - Kurboniyazov, G.A.; Atadjanova, D.A. (SCIENCE and SOCIETY, 2025)
This article discusses the “speech” conceptosphere in English and Karakalpak languages. It analyzes the usage, significance, and characteristics of the conceptual units within this sphere in both cultures. A comparative analysis of selected idioms related to this concept is also provided.